Combined Effect of Vertical and Horizontal Ground Motions on Failure Probability of RC Chimneys - Xuan Guo; Wei Chen; Jianbing Yu (Advances in Civil Engineering)
Previous earthquake events have shown that chimneys are one of the most fragile structures. Studies have focused on the seismic behavior of reinforced concrete (RC) chimney structures subjected to earthquake load only along the horizontal direction. However, the vertical component of strong ground motion has been proven to damage or completely destroy civil structures. Therefore, it is essential to determine the failure probability of RC chimneys under both horizontal and vertical directions. In this study, the seismic behavior of an RC chimney was studied through seismic fragility analysis, wherein a fragility model based on the intensity ratio between the vertical and horizontal components was proposed. In the fragility analysis, different intensity ratios of near-fault ground motions (NFGMs) between the vertical and horizontal components were considered. The findings indicate that the NFGMs along the vertical and horizontal directions significantly affect the failure probability if the intensity of the horizontal component is above a certain threshold. Moreover, the failure probability increases with the intensity of the vertical and horizontal ground motions. Therefore, the influence of the combination of the vertical and horizontal components of the NFGMs should be considered in the safety evaluation of RC chimney structures.